Faktor-Faktor Yang Mempengaruhi Ruptur Perineum Pada Ibu Bersalin Normal di Rumah Sakit Bhayangkara Mappaouddang Makassar Tahun 2014 - Candrayanti, Lilis (Journal of Islamic Medicine, 2019)
Background: Perineal rupture is a problem in labor and the second cause of bleeding after uterine atony. According to WHO in 2014 there were 2.7 million cases of Perineal Rupture in maternity mothers. Factors that can cause perineal rupture are parity, distance of birth, baby's weight, birth management is not as it should be, age, extraction, vacuum extraction, and episiotomy. Objective: For Factors Affecting Normal Perineal Rupture. Research Methods: This study is an analytic observational with a "cross sectional study" approach. The population, namely primigravida mothers who were treated in Bhayangkara Mappaouddang Makassar Hospital in 2014, amounted to 230 people. Sampling with purposive sampling technique amounted to 120 samples. Data using Chi-Square statistical test with P value 0.05). Results: There was an effect of maternal age on normal perineal rupture (P-Value = 0.003 0.05), there was an effect of infant birth weight on normal perineal rupture (P-Value = 0.003 0.05) ) and there is an influence of the recommended position to treat normal perineal rupture of primigravida mothers (P-Value = 0.004 0.05). Conclusion: There is an effect of maternal age, birth weight and recommended position with normal perineal rupture.Â Keywords: maternal age, baby's birth weight, , perineal rupture